Cancer during pregnancy and the postpartum period: A population‐based study. Issue 12 (3rd March 2015) - Andersson, Therese M.‐L.; Johansson, Anna L. V.; Fredriksson, Irma; Lambe, Mats
<x xml:space="preserve">Abstract</x> BACKGROUND The purpose of this study was to assess patterns of cancer occurrence during pregnancy and the postpartum period. METHODS This was a register‐based study using data from the Swedish Multi‐Generation Register and the National Cancer Register from 1963 to 2007. Pregnancy‐associated cancer (PAC) was defined as a malignancy detected during pregnancy or within 2 years of delivery and was assessed in 7 time windows: pregnancy, trimesters 1‐3, 0‐6 months, 7‐12 months, and second year postpartum. Population incidence rates by 5‐year age groups and periods were used to estimate the expected number of PACs for each site. The observed versus the expected (O/E) number of cases was estimated with 95% confidence intervals (CI). RESULTS The 3 most common malignancies during pregnancy were melanoma (n = 232), breast (n = 139) and cervical cancer (n = 139). With a slightly different rank order, these cancers are also the most common in women of childbearing age. The number of observed cases during pregnancy was lower than expected for all cancers, with a combined O/E ratio for all sites of 0.46 (95% CI, 0.43‐0.49). The O/E ratio was close to 1 during all postpartum intervals, including 0‐6 months (0.93; 95% CI, 0.88‐0.98), 7‐12 months (0.96; 95% CI, 0.91‐1.01), and during the second year after delivery (0.95; 95% CI, 0.92‐0.99). CONCLUSIONS The rate of cancer during pregnancy was lower than expected for all sites, a finding that could not be explained entirely by delayed diagnosis. A rebound in the number of observed cases after delivery was restricted to melanoma, nervous system malignancies, and breast and thyroid cancer. Cancer 2015;121:2072–2077. © 2015 American Cancer Society.